Analisis Puisi “Aku Tidak Akan Berhenti Mencarimu” Karya Heri Isnaini dengan Pendekatan Struktural - Siti Nurhalimah; Rianti Maryana (Universitas Palan, 2023)
Literary work is a form of expression of human feelings as outlined in oral and written forms. Literary work is a language art that can be enjoyed by oneself and for everyone to enjoy. Poetry is one type of kasya satsra which is an expression of the poet's feelings which is poured using figurative words. The poem entitled